2004
DOI: 10.1299/jsmeb.47.221
|View full text |Cite
|
Sign up to set email alerts
|

Flame Stability Limit and Exhaust Emissions of Low Calorific Fuel Combustion in Turbulent Diffusion Combustor for a Small-Scale Fuel Cell

Abstract: This paper describes an investigation conducted on flame stability and exhaust emissions from a turbulent diffusion combustor, fueled with low-calorific gas, for a small-scale fuel cell. It is important to maintain flame stability in the combustor, even under lean fuel conditions, and to suppress CO emission in the exhaust gas. An imitation off-gas, in which hydrogen and methane were diluted by adding nitrogen, with Wobbe indices ranging from ca. 4 400 -8 700, corresponding to the fuel utility ratio of 90% -60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…They found that the EPFM correctly predicted conditional and unconditional mean scalar structures, and allowed a detailed analysis of NOx formation mechanisms including thermal NO path, prompt and fuel NO formation, and reburn by hydrocarbon radicals, unlike the steady flamelet model. Numerous researches have investigated the NOx formation in different combustion regimes in the consequent few years [9][10][11][12][13][14][15][16][17]. The most intensive work, recently, on the numerical simulation of NOx prediction in gaseous flames was published by Lopez-Parra and Turan [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the EPFM correctly predicted conditional and unconditional mean scalar structures, and allowed a detailed analysis of NOx formation mechanisms including thermal NO path, prompt and fuel NO formation, and reburn by hydrocarbon radicals, unlike the steady flamelet model. Numerous researches have investigated the NOx formation in different combustion regimes in the consequent few years [9][10][11][12][13][14][15][16][17]. The most intensive work, recently, on the numerical simulation of NOx prediction in gaseous flames was published by Lopez-Parra and Turan [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…1 Experimental apparatus. (1) Pump for water, (2) pump for fuel, (3) mixer, (4) vaporisation unit, (5) inner pipe, (6) outer pipe, (7) catalyst, (8) electric heater, (9) gas burner, (10) thermal diffuser, (11) sheathed thermocouple,…”
mentioning
confidence: 99%
“…cold trap, (13) cooling system, (14) dryer, 高次炭化水素の液体燃料を使用した改質器の研究として,以下のものが挙げられる.Suzuki et al (3) は,ルテニ ウム触媒を用いた灯油の水蒸気改質時の触媒寿命について,報告している.Fukunaga et al (4) は,灯油を用いて, 脱硫吸着剤と水蒸気改質触媒を開発し,燃料処理システムをシミュレーションによって評価している.Kobori et al (5) は,n-ドデカンの水蒸気改質による動的パラメータを目安として,シミュレーションを行っている.齋藤と 氣仙 (6) は,灯油の吸着脱硫法および水蒸気改質法に着目し,長時間にわたり硫黄濃度を 0.05 ppm 以下に低減する 高性能な脱硫剤の開発と,高転化率で長寿命を示す改質触媒の開発について検討している.Liu et al (7) は,n-ドデ カンと n-ヘキサデカンをディーゼル燃料の代替物として用い,自熱改質を研究している.彼らは,反応温度と反 応生成物の関係,ならびに,改質器内部の温度分布を明らかにしている.Koseki (8) は,燃料電池改質器用燃焼器 として,実用灯油燃焼器にアノード・オフ・ガス用燃料ノズルと火炎安定用空気旋回器を追加した乱流拡散型燃 焼器を試作し,その基本燃焼特性について実験により検討している.Muramoto et al (9) は,ドデカン水蒸気改質反 応における Ru/CeO 2 /-Al 2 O 3 触媒の安定性を,触媒層に沿って複数のガス・サンプリング・ポートを備えた固定床 流通型の管型反応器を用いて,評価している.Yoon et al (10) は,1kW e 級の灯油水蒸気改質において,脱硫器操作 に必要な熱交換器を使用せずに灯油改質が可能かを検討している. これまで,高次炭化水素燃料の改質については,触媒自体の化学的研究,および,システム全体の理想状態で の理論シミュレーションによる評価が,主に行われてきた.しかし,実際の改質器については,あまり詳細な報 告がなされていない.そこで,本研究では,灯油等への応用を想定して,脱硫の必要がない n-ドデカン(C 12 H 26 )…”
unclassified
“…高次炭化水素の液体燃料を使用した改質器の研究としては,Suzuki et al (1) , Fukunaga et al (2) , Kobori et al (3) , 齋 藤と氣仙 (4) , Liu et al (5) , Koseki (6) , Muramoto et al (7) , Yoon et al (8) (1)…”
unclassified